Research on ciprofloxacin adsorption capacity of HKUDT-1 synthesized by electrochemical method - Hue, Le Thi; Phuong, Nguyen Thu; Thanh, Dinh Thi Mai; Thanh, Pham Thi Ha; Thi Kieu Anh , Nguyen (Vietnam Journal of Science and Technology, 2022)
Cu3(BTC)2 (or HKUST-1) is a metal-organic framework (MOF) material that was synthesized by electrochemical method from Cu and benzene-1,3,5-tricarboxylic acid with large surface area and high porosity. The influence of some factors on the adsorption of ciprofloxacin (CIP) by Cu3(BTC)2 such as pH (4 - 11), initial concentration of CIP solution (10 - 80 mg/L), mass of adsorbent (1 - 5 mg) and adsorption time (10 - 60 minutes) has been studied. The results showed that the highest CIP adsorption capacity of Cu3(BTC)2 was achieved at pH 7. When the mass of Cu3(BTC)2 adsorbent increased (19.6 - 100.2 mg/L), the CIP adsorption capacity decreased, and the CIP removal efficiency increased. With 39.4 mg/L of the adsorbent and 20 mg/L of the CIP solution, the CIP adsorption capacity was 238.44 mg/g and the CIP removal efficiency was 46.53 %. The adsorption process took place rapidly in the first 20 minutes then reached equilibrium after about 30 minutes. The study of adsorption kinetics and isothermal adsorption showed that the CIP adsorption process on Cu3(BTC)2 material is consistent with the pseudo-second-order kinetic model and the Langmuir model. The CIP adsorption mechanism of Cu3(BTC)2 is also shown: л - л interaction, hydrogen bond, and electrostatic interaction.